Health Inequities in LGBT People and Nursing Interventions to Reduce Them: A Systematic Review - Jorge Medina-Martínez (MDPI AG, 2021)
Background: Lesbian, gay, bisexual, and transgender (LGBT) people present poorer mental and physical health results compared to the heterosexual and cisgender population. There are barriers in the healthcare system that increase these health inequities. Objective: To synthesise the available evidence on how nurses can intervene in reducing health inequities in LGBT people, identifying their specific health needs and describing their experiences and perceptions of the barriers they face in the healthcare system. Methods: Systematic review. Between March and April 2021, a bibliographic search was carried out in the Cuiden, LILACS, PubMed, Dialnet, SciELO, Trip Database, and Web of Science databases and metasearch engines. Inclusion criteria: Articles published in the last 5 years that address the specific health needs of LGBT people, their experiences and perceptions, or interventions in this group in which nurses may engage. Results: A total of 16 articles were selected. Health disparities were detected in the LGBT community, which exhibited higher rates of mental health problems, substance abuse, risky sexual behaviours, self-harm, and suicide. These inequalities were related to minority stress, and each of them differently impacted individual populations within the broader LGBT community depending on their sexual orientations and gender identities. The impact of these factors was, in turn, modified by the intersections of race/ethnicity, geographic region, and socioeconomic factors. LGBT people described discriminatory experiences by health professionals, as well as their distrust and fear in this setting. Nurses can carry out interventions such as inclusive education about sex and sexual and gender diversity and bullying and suicide prevention programmes, and can provide gender-affirming and family-centred care. Conclusions: LGBT people experience health inequities and discrimination in the healthcare system. Nurses can implement diverse interventions to reduce these problems and, moreover, these health professionals are obliged to acquire cultural competence regarding LGBT health.